The Role of Institutional Ownership Moderation in the Relationship Between Financial Ratios and Financial Distress - Emillia Sastrasasmita; Chelsya Chelsya; Kartini Kartini; Sri Sundari (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the effect of multidimensional financial ratios on corporate financial health, proxied by the Altman Z-Score, and to analyze the moderating role of institutional ownership in non-cyclical consumer-sector companies listed on the Indonesia Stock Exchange during 2022–2024. Research Method: This study employs a quantitative research design using panel data regression and Moderated Regression Analysis (MRA). The sample was selected through purposive sampling based on the availability of annual financial reports. The independent variables include liquidity, profitability, solvency, leverage, operational efficiency, and firm size, while corporate financial health is measured using the Altman Z-Score. Institutional ownership is used as a moderating variable. Results and Discussion: The findings reveal that profitability, measured by return on assets, and operational efficiency, measured by total asset turnover, have a significant positive effect on the Altman Z-Score. Meanwhile, liquidity, solvency, leverage, and firm size do not significantly affect financial health. Institutional ownership weakens the relationship between profitability and the Altman Z-Score. Implications: The findings suggest that institutional ownership may function as a substitute monitoring mechanism rather than always strengthening financial signals. Originality: This study contributes by integrating multidimensional financial ratios, the Altman Z-Score, and institutional ownership to assess financial health in Indonesia’s non-cyclical consumer sector.